The mediating role of psychological commitment between recreation specialization and life satisfaction: Evidence from Xiamen Marathon runners - Tian, Haibo; Zhou, Wenting; Qiu, Yajun (Frontiers in Psychology, 2022)
Although previous researches spared no efforts to explain the life satisfaction of marathon runners, little was known about the relationship between recreation specialization (RS), life satisfaction (LS), psychological commitment (PC), and social support (SS). This study examines ⅰ) how the dimension of RS (i.e., behavior, cognition, and affect) influence runners’ PC and LS, and ⅱ) the mediating effects of PC and the moderating effects of SS on the relationship between behavior, cognition, affect and LS. The results showed that behavior, cognition, affect, and PC had significant and positive impacts on runners’ LS; PC mediated the relationship between the dimensions of RS and LS. In addition, the results also confirmed the moderating effects of SS between affect dimension and LS. These findings shed new light for understanding how RS dimensions and PC influence runners’ LS. The implications and limitations of this study were discussed.